Perencanaan Tebal Perkerasan Kaku (Rigid Pavement) pada Jalan Perkebunan Lestari Desa Sungai Awan Kiri Kabupaten Ketapang - Firza, Muhammad; Yustinus, Yoseph; Kamil, Firmanilah; Ir. Yustinus, Yoseph (Journal of Research and Inovation in Civil Engineering as Applied Science (RIGID), 2026)
Perkebunan Lestari Road is a local road that functions as public access to plantation and residential areas in Sungai Awan Kiri Village, Muara Pawan District, Ketapang Regency, West Kalimantan, Indonesia. The existing road condition is an unpaved dirt surface that suffers severe damage, particularly during the rainy season, resulting in reduced accessibility and vehicle comfort. This condition highlights the need for proper pavement planning to support transportation activities and local economic development. This study aims to determine the Average Daily Traffic (LHRN), evaluate the subgrade bearing capacity based on the California Bearing Ratio (CBR), design the rigid pavement thickness, prepare planning drawings, and estimate the construction budget for the development of Perkebunan Lestari Road. The research employed a quantitative approach with data collection through field observation, literature review, and documentation. The rigid pavement thickness design refers to the Indonesian National Standard SNI 8457:2017 Pavement Design Catalog, considering road classification and traffic loading. Field investigation results indicate a planned rigid pavement length of 500 m and a width of 3 m. The analysis shows that the LHRN value is 0.67 vehicles, indicating low traffic volume, while the average CBR value of the subgrade soil is 6.64%, representing moderate soil strength. Based on these parameters, the pavement structure consists of a 0.05 m thick lean concrete layer and a 0.15 m thick concrete slab. The estimated total construction cost for the rigid pavement is IDR 619,012,526.00. The proposed pavement design is expected to improve road performance, enhance traffic flow, and support plantation and community activities along the road.